Evidence of Helicobacter spp. in Saliva and Gastric Mucosa of Domestic Dogs in the Central Region of Rio Grande do Sul, Brazil - Daniel D. Guerra Segundo; Camila B. E. Mello; Juliana F. Cargnelutti; Mariana M. Flores; Luís F. Pedrotti; Bernardo N. Antunes; Vanessa Milech; Omar G. Velasquez; Letícia R. Martins; Saulo T. L. Pinto Filho (Veterinary Medicine International)
Helicobacter pylori is a spiral-shaped bacterium, which plays a role in the aetiology of gastric diseases in humans. Non-H. pylori Helicobacter (NHPH) species naturally colonise the stomach of animals and also induce gastric lesions in humans, highlighting their zoonotic importance. We evaluated the gastric bacterial colonisation density and gastric lesions and sought to identify the main phylogenetic groups of the Helicobacter spp. obtained from dogs in the central region of Rio Grande do Sul, Brazil, with this study aiming to investigate the occurrence of Helicobacter spp. in saliva and gastric samples from these dogs. This study included 35 dogs and used analysis such as cytology, histopathology, PCR, rapid urease testing, and phylogenetic analysis. Of the dogs, 94.3% were positive for Helicobacter spp., and these bacteria were present in the stomach of 32 dogs and saliva of eight. Respectively, eight, 15, and nine dogs had mild, moderate, and severe colonisation. Lymphocytic-plasmacytic infiltrate was the main gastric lesion. However, the presence of Helicobacter and the density appeared to be unrelated to the gastric lesions. The samples possessed a high nucleotide identity with remarkably similar sequences among some of the species of NHPH such as H. heilmannii s.s., H. salomonis, H. felis, and H. bizzozeronii. The saliva of domestic dogs, even of those who appear clinically healthy, can cause Helicobacter infection in humans and other animals, with, in these dogs, increased density, occurrence rate, and predominance of NHPH of zoonotic importance being found in the stomach with a lower occurrence of Helicobacter spp. in the saliva.